Pengaruh Kualitas Pelayanan Dan Potonngan Harga Terhadap Kepuasaan Pelanggan GoFood (survey Pada Follower Akun Instagram @gofoodindonesia) - Alviana Hikmawati; Liya Megawati (Peneliti.net, 2022)
This study aims to determine the relationship between service quality and price discount, the effect of service quality and price discount on customer satisfaction partially, and the effect of service quality and price discount on customer satisfaction simultaneously.This study uses quantitative approach with descriptive and verification methods. The populations of this study is the instagram followers of @gofoodindonesia who use GoFood application with 384 sample. This study uses non-probability sampling with purposive sampling as a method. The analysis that used in this study is path analysis with SPSS 25 as a tool.The results shows that there is positive and strong enough correlation between service quality and price discount by 0,559. Partially, service quality has positive and significant effect on customer satisfaction by 0,414 and partially price discount has positive and significant effect on customer satisfaction by 0,133. Simultaneously, service quality and price discount have positive and significant effect on customer satisfaction by 0,547